ChemInform Abstract: Grevillosides J—Q, Arbutin Derivatives from the Leaves of Grevillea robusta and Their Melanogenesis Inhibitory Activity. Issue 38 (10th September 2014) - Yamashita‐Higuchi, Yukiko; Sugimoto, Sachiko; Matsunami, Katsuyoshi; Otsuka, Hideaki; Nakai, Takahito
Abstract New arbutin derivatives grevillosides J—Q (I), (II), are isolated along with eight known compunds from the leaves of Grevillea robusta.